Pelatihan Pencegahan Penyakit Kuku Akibat Jamur bagi Pemulung Sampah di Tempat Pembuangan Akhir (TPA) Sumompo Kota Manado - Pinontoan, Sabrina Prisscilya Magdalena; Febriana, Befani Adhitya; Andaria, Allan J. (Jurnal Pengabdian UNDIKMA, 2024)
This service activity seeks to improve garbage scavengers' knowledge and skills in preventing nail disease caused by fungi in the Sumompo Final Disposal Site (TPA) environment in Manado City. The method of implementing this service is through training and discussion, with leaflets serving as the learning medium. Meanwhile, fungal examinations use the direct procedure involving KOH. Training activities are evaluated using pre-test and post-test techniques, which are then analyzed descriptively. The evaluation results show that the average pre-test score is 44.89, and the average post-test score is 78.89, showing a 34.00 gain in knowledge following training. The findings of the practical exercises revealed that numerous individuals displayed clinical characteristics/symptoms of fungal nail disease, such as dull, thickened, uneven, cracked nails, and color changes from white to caustic, brown to black. Examination of nail scraping samples from 14 individuals with atypical nails revealed that all samples tested positive for hyphae and/or spores.Â 